Simvastatin inhibits the immunosuppressive effects of endometrial cancer-associated mesenchymal stem cells through TGF-β2/SMAD2/3 signaling and reduces tumor growth - Kai-Hung Wang; Yu-Hsun Chang; Dah-Ching Ding (Scientific Reports)
Abstract Simvastatin, a 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase inhibitor, was used in cardiovascular diseases and could decrease low-density lipoprotein cholesterol, and may have a repurposed role in cancer therapy. However, the effects of simvastatin on endometrial cancer remain controversial. We aimed to elucidate the role and mechanisms of simvastatin in regulating previously identified endometrial cancer-associated mesenchymal stem cells (EmCaMSCs)-mediated immunosuppressive effects and anti-tumor progression. Coculture of EmCaMSCs and peripheral blood mononuclear cells (PBMC) was used to assay the population of CD8 + T cells, natural killer (NK) cells, and cytotoxicity of NK cells. The mechanisms were elucidated by applying recombinant proteins and inhibitors of candidate proteins, transforming growth factor-beta 2 (TGF-β2). Finally, the humanized mouse model was generated to study the effects of simvastatin-mediated immunotherapy in treating endometrial cancer. The protein expressions of TGF-β2, CD56, CD8, and PD-L1 in xenograft tumors were analyzed by Western blot or immunohistochemistry assay. In this study, simvastatin inhibited the proliferation of endometrial cancer cells (HEC-1 A and RL95-2) and EmCaMSCs, and the half-maximal inhibitory concentration (IC50) values of EmCaMSCs were much higher. Simvastatin rescued the proliferation and the population of CD8 + T cells and natural killer (NK) cells from PBMC coculturing with EmCaMSC. Simvastatin treatment reduced the expression of TGF-β2 in EmCaMSCs at both the gene and protein levels. TGF-β2 activated the downstream SMAD2/3 signaling, and their inhibition by simvastatin could enhance the cytotoxicity of NK cells against endometrial cancer cells in vitro. Additionally, a combination of simvastatin and NK cell therapy inhibited xenograft growth, potentially by reducing TGF-β2 expression. In conclusion, simvastatin could rescue the population of CD8 + T cells and NK cells from PBMC cocultured with EmCaMSCs. Furthermore, simvastatin could enhance the cytotoxicity of NK cells in vitro and inhibit tumor growth in vivo in a humanized mouse model. These results suggested that simvastatin may be considered as a repurposed and combination drug for treating endometrial cancer.